Legal determinations of the place and role of the Intelligence and Security Agency of Bosnia and Herzegovina - Alispahić, Bakir (Technium Social Sciences Journal, 2021)
One of the main principles of the work of security services is the principle of legality. However, as the basic task of the security services is to take care of the security of the democratic order, the security services are expected to act transparently and respect the laws in their work. In this sense, it is very important to clearly define the place and role of the security service itself within the legal framework. The Law on the Intelligence and Security Agency of BiH was adopted in 2004 and prescribed the standards and solutions that the Intelligence and Security Agency of BiH must adhere to if it wants to be professional. In accordance with that, and the sensitive nature of the role in the national security system, the analysis of the legal determinations of the place and role of the Intelligence and Security Agency of BiH in fulfilling the obligations of cooperation with domestic and international institutions is imperative. To understand the place and role of the BiH Intelligence and Security Agency, it is crucial to determine its legal position and status in the national legal system. Both ‘general’ and ‘special’ mechanisms of cooperation with domestic and international standards depend on the legal position of the Agency.